The abyssal voyage of the argonauts: Deep-sea in situ observations reveal the contribution of cephalopod egg cases to the carbon pump. (May 2022) - Hoving, H.J.T.; Amon, D.; Bodur, Y.; Haeckel, M.; Jones, D.O.B.; Neitzel, P.; Simon-Lledó, E.; Smith, C.R.; Stauffer, J.B.; Sweetman, A.K.; Purser, A.
Abstract: Calcifying plankton in the upper ocean produce calcium carbonate (CaCO3 ) shells that sink to the seafloor after death resulting in the vertical transport of inorganic carbon in shells and organic carbon in carcasses. In situ observations of pelagic detritus on the abyssal plain are very scarce. Carcasses are rapidly scavenged and shells may dissolve owing to undersaturation of deep waters with respect to CaCO3 . We observed more than 300 egg cases of the epipelagic cephalopod Argonauta sp. in 9 large seafloor image surveys investigated across the Clarion Clipperton Zone in the Pacific between 2010 and 2020. Females of this octopus produce calcite egg cases that are used for buoyancy and as substrate on which to attach their eggs in the water column. These cases sink to the seafloor, presumably upon death of the octopus. In one area, between 3970 and 4551 m water depth surveyed in 2019, we documented more than 200 complete and fragments of egg cases (5.84 ± 1.8 cm in size) on the seafloor, complete and broken and in various states of dissolution. Here, we present observations of egg case dissolution in situ and of 99 white deposits that were likely largely dissolved egg cases. Our observations reveal a previously undocumented pathway of epipelagic inorganic carbon to the abyssal plain. Preliminary estimations indicate that the local contribution of Argonauta egg cases to the vertical transport of carbonates is likely small compared to other planktonic calcifiers, but the geographic extent of the deposition in the eastern Pacific is apparently large. This study highlights the need for in situ observations to discover and document carbon fluxes in the deep sea, and for consideration of life history traits in unraveling elusive pathways within the biological pump. Highlights: Camera observations document regional deposition of cephalopod remains on the abyssal plain. More than 300 Argonauta egg cases were observed at 3970–4551 m in the central east Pacific between 2010 and 2020. Shells were in various states of disintegration owing to damage, scavenging and dissolution. Sinking epipelagic Argonauta egg cases to abyssal depths is a pathway in the carbon pump. In situ observations show that shell decomposition takes about 90 days in this region.